Thinking Religion Through Things: Reflections on the Material Turn in the Scientific Study of Religion\s - Bräunlein, Peter J. (Method & theory in the study of religion, 2016)
In recent years, the “material turn” has gained prominence in the humanities and social sciences, and it has also stimulated a shift toward a rediscovery of materiality in the scientific study of religion\s. The material turn aims to dissolve conventional dichotomies and, by emphasizing the concept of assemblage, insists that humans and things are fundamentally co-constitutive. This “New Materialism” addresses ontological alterity, and it radically decenters static anthropocentric arrangements and the position of the human subject as such. The insider–outsider distinction, however, as well as the emic–etic categorization, are based on fundamental dichotomies between the researcher and the researched, and between descriptive and analytical understandings of human beings. This article discusses the possibility and significance of a non-anthropocentric approach to religion, and examines to what extent it is analytically helpful to apply the insider–outsider and emic–etic distinctions while pursuing the goal of dissolving hierarchical and binary thinking. It furthermore argues that these issues can be properly answered only with reference to their methodological implications.